Lost and Found: Taxonomic revision of the speckled skink (Oligosoma infrapunctatum; Reptilia; Scincidae) species complex from New Zealand reveals a potential cryptic extinction, resurrection of two species, and description of three new species - Melzer, Sabine; Hitchmough, Rod A.; Bell, Trent; Chapple, David G.; Patterson, Geoff B. (Zootaxa, 2019)
New Zealand has a diverse skink fauna, comprising 45 described native species, and at least 15 undescribed taxa, within the single genus Oligosoma Girard, 1857. One of the earliest described, and best known, species is the speckled skink, Oligosoma infrapunctatum (Boulenger 1887). Despite a relatively stable taxonomic history for nearly 114 years, recent molecular work has indicated that O. infrapunctatum represents a species complex, comprising numerous genetically divergent, range restricted taxa. We completed the first stage of a taxonomic revision of O. infrapunctatum, conducting a morphological re-evaluation of existing voucher material, and newly collected specimens, and generated a molecular phylogeny for the species complex. This allowed us to distinguish six species: O. infrapunctatum, two species resurrected from synonymy (O. newmani, O. robinsoni), and three new species (O. salmo sp. nov., O. albornense sp. nov. O. auroraensis sp. nov.). The name bearing type population of O. infrapunctatum has not been located again for at least 130 years: it remains to be rediscovered and may already be extinct. Two of the six species here are considered ‘Nationally Critical’ (O. albornense sp. nov., O. salmo sp. nov.) under the New Zealand Threat Classification System, the others are Nationally Vulnerable (O. auroraensis sp. nov.) and At Risk—Relict (O. newmani, O. robinsoni). Further taxonomic work will be required to determine the taxonomy of other speckled skink genetic lineages in the South Island, particularly O. aff. infrapunctatum “cobble”, O. “Hokitika”, O. “Southern North Island” and O. “Westport”.